Proses Penjualan Ikan di Desa Tanjung Medang Kecamatan Rangsang Kabupaten Kepulauan Meranti, Provinsi Riau - Derry Agustian; Eni Yulinda; Firman Nugroho (Berkala Perikanan Terubuk, 2015)
This study was conducted in October 2013. The aimed of this research to determined how the marketing constraints processed fish, comparing the costrequired by each institution marketing of processed fish, and know the marketing margin and marketing processe fish, known the big profit margin earned by the traderson the marketing of processed fish in the village of Tanjung Medang. The method used in this study is the method of survey respondents by the number offish processors and the number of 12 people who work astradersa mounted to 5 people.  Marketing costs were influenced by the distance of the village of Tanjung Medang to destination marketing, was further influenced by theamount of fish taken orpurchased more and more fish were purchased then its fixed costs will be greater as well. The total cost of marketing every different marketing agency that was highest on the total marketing cost collector was equal to four Rp 50.428.332/month , because these carry traders into four Regions of processed fish to Bengkalis so much so that the greater the total cost was found , while the lowest total cost of marketing was the first collector Rp 39.128.332/month with total revenues, and the value of marketing margins in the village of Tanjung Medang very different, for the highest value of marketing margins in the second collector as much as 68.9 % with the type of fish Lomek processed, while the lowest marketing margin on the first collector as much as 35.9 % with the type of fish processed chicken feathers and marketing agencies value the highest profit margin obtained by the two traders to profit margins Rp 8.979/kg value to the marketing area of Malaysia, while the profit margin for the lowest value obtained by the first traders to profit margin value of Rp 2.255/kg to Tanjung Balai Karimun marketing area.